Visual Recognition of Child Body Mass Index by Medical Students, Resident Physicians, and Community Physicians - Ahlers-Schmidt, Carolyn R; Kroeker, Deborah; Chesser, Amy; Hart, Traci; Brannon, Jennifer (Kansas Journal of Medicine, 2010)
Background: Many studies have assessed the ability of mothers to identify their child’s Body Mass Index (BMI) category and the vast majority of mothers are unable to do so accurately. This suggested a need for physicians to inform parents about their child’s weight status. However, many physicians do not chart BMI-for-age, even though it is recommended. Instead they rely on their visual perception of the patient’s weight status. This study determined the number of medical students, resident physicians, and community physicians who correctly categorize preschool children into their appropriate weight class by visual cues alone. Methods: Fourth-year medical students, family medicine and pediatric resident physicians, and family medicine and pediatric community physicians completed a brief on-line survey. Pictures of three preschool children were shown and respondents described each child’s BMI-for-age category. Results: A 43% (134/312) response rate was achieved. Only 15% of respondents correctly identified a 3-year-old boy, whose BMI was >95th percentile for his age, as obese. Nearly 86% correctly identified a 4-year-old girl with normal BMI-for-age, but only 21% correctly identified another girl who was overweight at the 90-95th percentile BMI-for-age. No significant difference was found in total accuracy between medical students, resident physicians, or community physicians (F(2,123)=0.743, p=0.478) or between family medicine physicians and pediatricians (F(1,107)=2.269, p=0.135) when predicting the BMI-for-age categories. Conclusions: Medical professionals and trainees have difficulty visually assessing a child’s BMI-for-age weight status. This underscores the importance of calculating and plotting BMI at healthy check-ups.